Translation and Validation of a Brief Health Literacy Instrument for School-Age Children in a Danish Context - Ane H. Bonde; Nanna W. Stjernqvist; Charlotte D. Klinker; Helle T. Maindal; Olli Paakkari; Peter Elsborg (SLACK Incorporated, 2022)
Low health literacy (HL) is associated with adverse health behaviors and poor health, and brief, high-quality instruments for measuring HL in children are scarce. The Health Literacy for School-Aged Children (HLSAC) instrument is a 10-item theory-based and internationally validated tool for measuring HL. The purpose of this study was to translate and validate the HLSAC instrument among Danish school-aged children. The instrument was translated into Danish by a standardized forward-backward translation process, and then pre-tested for face validity with 61 pupils from four schools. Thereafter, the instrument was tested among 805 pupils in grades 6 to 7 (age 11-14 years) from 15 schools. When HL was modeled as one latent factor with all 10 items loading on this factor, the confirmative factor analysis showed standardized factor loadings from 0.52 to 0.75 (p < .001) and an excellent model fit. The association between HL and food intake as a health behavior example (p < .001, r2 = .027) indicates the predictive validity of the instrument. The internal consistency was high (Cronbach's alpha = 0.86). Thus, a valid and reliable version of the HLSAC instrument is available in Danish for future surveys to monitor HL and guide health promotion targeting children and adolescents. [HLRP: Health Literacy Research and Practice. 2022;6(1):e25-e29.]